Review paperTopical calcineurin inhibitors in dermatology. Part I: Properties, method and effectiveness of drug use - Gutfreund, Katarzyna; Bienias, Wojciech; Szewczyk, Anna; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Topical calcineurin inhibitors (TCI) are a relatively new class of drugs used in dermatology. There are two drug forms available – tacrolimus 0.03% or 0.1% ointment and 1.0% pimecrolimus cream. The drugs act by inhibiting synthesis of proinflammatory cytokines. The only approved indication for using TCI is treatment of atopic dermatitis. The TCI may be used as an alternative therapy to corticosteroids. Tacrolimus is used to treat moderate-to-severe atopic dermatitis, pimecrolimus – mild-to-moderate atopic dermatitis. Topical calcineurin inhibitors do not cause skin atrophy and the drug absorption through the skin is minimal. The TCI have been well-studied, their efficacy was evaluated in a number of vast, long-term studies. The anti-inflammatory potency of tacrolimus ointment is similar to a corticosteroid with moderate activity, while the latter is clearly more active than pimecrolimus cream. Topical calcineurin inhibitors significantly relieve pruritus in atopic eczema.